The Application Of Technical Trading Rules: A Comparative Study Between Six Equity Markets In Middle East - Baghini, Hussein Najmizadeh (2007)
The empirical evidence of the study contributes in-depth understandings on the predictive ability of this simple and popular technical trading rule in emerging markets of Middle East.